2020
DOI: 10.3390/app10175973
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Stress Field in Peri-Implant Bone: A Parametric Study of Influencing Parameters and Their Interactions for Multi-Objective Optimization

Abstract: The present work proposes a parametric finite element model of the general case of a single loaded dental implant. The objective is to estimate and quantify the main effects of several parameters on stress distribution and load transfer between a loaded dental implant and its surrounding bone. The interactions between them are particularly investigated. Seven parameters (implant design and material) were considered as input variables to build the parametric finite element model: the implant diameter, length, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…People who suffer from osteoporosis will inevitably have less bone stiffness, are more prone to fracture [54]. Bone quality has been examined in many studies using finite element methods [55][56][57]. Our findings concur with their conclusion that deterioration in bone quality precedes a worsening of stress and strain.…”
Section: Discussionsupporting
confidence: 87%
“…People who suffer from osteoporosis will inevitably have less bone stiffness, are more prone to fracture [54]. Bone quality has been examined in many studies using finite element methods [55][56][57]. Our findings concur with their conclusion that deterioration in bone quality precedes a worsening of stress and strain.…”
Section: Discussionsupporting
confidence: 87%
“…An example of finite element model is shown in Fig. (2) and it consists of the cortical, cancellous bone an implant and abutment [16]. The model is designed from a numerical strategy from the assembly of the different parts together and the stress distribution is studied.…”
Section: Mechanical Properties Of Bone Teeth Biomaterials For Finite Element Modelingmentioning
confidence: 99%
“…The implant diameter, length, loading angle, and insertion depth has an effect on the stress distribution [8,25]. Didier et al [16] investigated the several parameters (implant diameter, length, angle of inclination, taper, Young's modulus, the thickness of the cortical bone, and Young's modulus of the cancellous bone) on stress distribution and load transfer between the dental implant and bone using a FE model. They found that the implant diameter and Young's modulus and the cortical thickness were the most influential parameters on the two responses.…”
Section: Factors Affecting the Stress Distri-bution Around Implantmentioning
confidence: 99%
“…K Bouzouina and al [20] Have studied the biomechanical behavior of dental implants has been compared by the finite element method. P Didier and al [21] Have proposed a parametric model by the method of finite elements for the general case of a dental implant loaded. Unfortunately, some complications can occur, such that a failure of osseointegration.…”
Section: Introductionmentioning
confidence: 99%